2020
DOI: 10.1109/jstars.2020.3034432
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Enhanced SMOS Level-2 Ocean Salinity Product

Abstract: The quality of the Soil Moisture and Ocean Salinity (SMOS) Sea Surface Salinity (SSS) measurements has been noticeably improved in the last years. However, for some applications, there are still some limitations in the use of the level 2 ocean salinity product. First, the SSS measurements are still affected by a latitudinal and seasonal bias. Second, the high standard deviation of the SSS error could significantly degrade part of the SSS signal.Last, the coverage of the level 2 salinity measurements is signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The original approach leads in the Black Sea to SMOS SSS fields with seasonal biases much larger than the expected ones in global ocean (see the biases of Figure 7 in comparison with the ones reported in (Olmedo et al, 2020(Olmedo et al, , 2021a). The cause of the seasonal biases is not completely understood although some authors associate the origin to SST-depending errors in the salinity retrieval (Le Vine et al, 2015).…”
Section: Bias Characterization Depending On the Sstmentioning
confidence: 81%
See 2 more Smart Citations
“…The original approach leads in the Black Sea to SMOS SSS fields with seasonal biases much larger than the expected ones in global ocean (see the biases of Figure 7 in comparison with the ones reported in (Olmedo et al, 2020(Olmedo et al, , 2021a). The cause of the seasonal biases is not completely understood although some authors associate the origin to SST-depending errors in the salinity retrieval (Le Vine et al, 2015).…”
Section: Bias Characterization Depending On the Sstmentioning
confidence: 81%
“…We use the debiased non-Bayesian retrieval (Olmedo et al, 2017) because: i) this approach properly mitigates the systematic biases coming from the residual LSC and permantent RFI sources; and ii) it improves the coverage of the good quality SSS retrievals in comparison with the standard (Bayesian) retrieval approach (Olmedo et al, 2020). The debiased non-Bayesian (DNB) approach (Olmedo et al, 2017(Olmedo et al, , 2021a has been fine-tuned for retrieving SSS in the Black Sea.…”
Section: Sss Retrieval Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…At the SSS level, global comparisons (60 • S-60 • N) with in situ data provided by Argo floats show a significant improvement in NS SSS wit a Root Mean Square (RMS) equal to 0.81 with respect to the SSS from the current operational TBs (RMS = 1.09). Global comparisons to data from ship tracks show also a slight improvement in terms of RMS when applying NS (RMS = 1.82 and a correlation coefficient of 0.61) with respect to the SSS from the current operational TBs (RMS = 1.87 and correlation coefficient R = 0.55).It must be pointed out that the spatial coverage of SSS retrievals from the corrected NS TBs increases by 20% on average with respect to the SSS from the current operational TBs, particularly over semi-enclosed seas and strongly RFI-contaminated regions [20].…”
Section: Nodal Sampling: Reduction Of Rfi Contamination In Smos Imagesmentioning
confidence: 90%
“…When we applied the original DNB retrieval to the Baltic Sea, we observed that seasonal variations were much higher than in the global ocean (Olmedo et al, 2020) and a non-expected spatial gradient appeared close to the coasts. These effects were evidenced when computing the monthly mean difference between SMOS SSS and CMEMS Baltic reanalysis salinity field (Figure 4).…”
Section: Definition Of a Smos-based Climatologymentioning
confidence: 93%